2020
DOI: 10.1093/esr/jcaa011
|View full text |Cite
|
Sign up to set email alerts
|

Early Careers of Dropouts from Vocational Training: Signals, Human Capital Formation, and Training Firms

Abstract: Dropping out of post-secondary education has negative consequences for career progression. However, as human capital theory predicts and as previous studies have shown, having some training still pays off. For a large part of the European workforce who has attended vocational training, however, the theoretical predictions are less clear and empirical studies are scarce. In occupational labour markets, signalling and credentialism theories predict negative effects of dropping out. Furthermore, apprenticeship dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…School certificates are strongly related to NEET risks (OECD, 2016: 24). This might be especially relevant in the highly credentialised German context where school certificates are very decisive for access to VET programmes (Holtmann et al, 2017), which are, in turn, important for successful labour market entry (Patzina and Wydra-Somaggio, 2020).…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…School certificates are strongly related to NEET risks (OECD, 2016: 24). This might be especially relevant in the highly credentialised German context where school certificates are very decisive for access to VET programmes (Holtmann et al, 2017), which are, in turn, important for successful labour market entry (Patzina and Wydra-Somaggio, 2020).…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Både norsk og internasjonal forskning viser til viktigheten av å vaere formelt kvalifisert til deltakelse i arbeidslivet ved å ha vitnemål eller kompetansebevis. Uten dette, kan hindringer på veien mot varig arbeidslivstilknytning vaere spesielt store (NOU 2001: 22;NOU 2018:2;Patzina & Wydra-Somaggio, 2020). Frøseth (2008) og Markussen (2014) har gjort funn som sammenfaller med dette.…”
Section: Verdig Voksenlivunclassified
“…Human capital theory (e.g., Becker, 1964), signaling theory (e.g., Spence, 1973), and credentialing theory (e.g., Collins, 1979) have provided the main theoretical explanations for differences in short-and long-term labor market outcomes for different educational groups. Empirical findings from the "school-to-work transition" literature have supported these theoretical notions since studies in this area have emphasized the fact that the attainment of signals and credentials is of pivotal importance for successful transitions into the labor market (e.g., Fossati et al, 2020;Jacob & Solga, 2015;Patzina & Wydra-Somaggio, 2020). Additionally, the literature has provided evidence for the notion of human capital and has indicated that school performance (i.e., good grades) in upper-secondary education predicts high wages at the time of labor market entry (e.g., Wydra-Somaggio & Seibert, 2010).…”
Section: Introductionmentioning
confidence: 96%